Mahuang Decoction Antagonizes Acute Liver Failure via Modulating Tricarboxylic Acid Cycle and Amino Acids Metabolism - Liao, Wenting; Jin, Qiwen; Liu, Junning; Ruan, Yiling; Li, Xinran; Shen, Yueyue; Zhang, Zhicheng; Wang, Yong; Wu, Shengming; Zhang, Junying; Kang, Lifeng; Wu, Chunyong (Frontiers in Pharmacology, 2021)
Acute liver failure (ALF) is a life-threatening clinical syndrome with high fatality rates. Mahuang decoction (MHD), a well-known traditional Chinese medicine, has multiple pharmacological effects, such as anti-inflammation, anti-allergy, anti-asthma, and anti-hyperglycemia. In this study, we investigated the protective effect of MHD against ALF. In the ALF mouse model induced by lipopolysaccharide and D-galactosamine (LPS/D-GalN), the elevated activities of the serum alanine and aspartate transaminases as well as the liver pathological damage were markedly alleviated by MHD. Subsequently, ultrahigh performance liquid chromatography-Q Exactive Orbitrap mass spectrometry-based metabolomics study was carried to clarify the therapeutic mechanisms of MHD against ALF. A total of 36 metabolites contributing to LPS/D-GalN-induced ALF were identified in the serum samples, among which the abnormalities of 27 metabolites were ameliorated by MHD. Metabolic pathway analysis revealed that the therapeutic effects of MHD may be attributed to modulating the metabolic disorders of tricarboxylic acid (TCA) cycle, retinol metabolism, tryptophan metabolism, arginine and proline metabolism, nicotinate and nicotinamide metabolism, phenylalanine metabolism, phenylalanine, tyrosine and tryptophan synthesis, and cysteine and methionine metabolism. This study demonstrated for the first time that MHD exerted an obvious protective effect against ALF mainly through the regulation of TCA cycle and amino acid metabolism, highlighting the importance of metabolomics as a potential tool to investigate drug-targeted metabolic pathways.